Treatment of Hypertension: Is There a Place for Personalization of the Approach in Modern Recommendations? - V. I. Podzolkov; A. E. Bragina; Yu. N. Rodionova (Рациональная фармакотерапия в кардиологии)
The important result of the revision of the European and Russian guidelines for the management of arterial hypertension was a conclusion about the need to use a double combination of antihypertensive drugs as the first stage of antihypertensive therapy. The review presents benefits of combined antihypertensive therapy, confirmed by the results of randomized clinical trials and meta-analysis. There are literature data suggesting one of the first line reasonable combinations is the combination of angiotensin converting enzyme inhibitors (ACEI) and thiazide-like diuretic. The article discusses the benefits of single-pill combinations before free ones, such as increase in patient adherence to long-term treatment, reduction in the cost of the drug and the number of tablets. As an example, a highly effective single-pill combination of one of the most used ACEI, lisinopril and indapamide sustained release, is considered, which has protective activity, vasodilator properties and metabolic neutrality. The article presents the data of the PIFAGOR IV study that indapamide is the most widely used diuretic in Russia, which is characterized by high antihypertensive efficacy, good tolerance, cardioprotective, nephroprotective and osteoprotective properties. The results of large-scale studies, which show the ability of lisinopril to retain target blood pressure level, antiproteinuric and cardioprotective activity, are also presented. This single-pill combination has a long additive effect, contributing to reliable daily monitoring of blood pressure. The authors expressed the opinion that the prescription of highly effective single-pill combinations will contribute to organ protection and reduce the risk of cardiovascular complications development.